Application of zirconium-based metal organic framework in PET plastic degradation, molybdenum-loaded zirconium-based metal organic framework and preparation method of molybdenum-loaded zirconium-based metal organic framework

By using zirconium-based metal organic frame NU-1000 and its derivatives to catalyze the degradation of PET plastics, the problem of harsh chemical recycling conditions of PET plastics and difficult to separate the degradation products in the prior art is solved, and efficient, safe and environmentally friendly degradation effect of PET plastics is achieved.

CN119500266APending Publication Date: 2025-02-25GUANGZHOU UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411655048.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing chemical recycling methods for PET plastics have problems such as harsh conditions and difficulty in separation and purification of degradation products.

Method used

The zirconium-based metal organic framework NU-1000 with good chemical and thermal stability is adopted, and the degradation of PET plastics is achieved under a solvent-free and atmospheric pressure by activating by loading Mo metal and high temperature hydrogen.

Benefits of technology

While simplifying the degradation process of PET plastics, the degradation conversion rate is improved, the degradation products are easy to be separated and recovered, and the catalyst is completely separated from the degradation products, making it easy to be recycled and reused.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500266A_ABST
    Figure CN119500266A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of plastic garbage recovery, and discloses application of a zirconium-based metal organic framework in PET (polyethylene terephthalate) plastic degradation, a molybdenum-loaded zirconium-based metal organic framework and a preparation method of the molybdenum-loaded zirconium-based metal organic framework. A zirconium-based metal organic framework is used as a catalyst to catalytically degrade PET plastic, the zirconium-based metal organic framework is at least one of NU-1000, Mo-NU-1000 and Mo-NU-1000-H2, the atmosphere for catalytic degradation is hydrogen or nitrogen, and the addition amount of the catalyst is 1.5-5 mol% of the use amount of the PET plastic. According to the invention, a solvent-free, high-temperature-free and high-pressure-free degradation method is used, the three materials have catalytic degradation effects on the PET plastic in a hydrogen or nitrogen atmosphere, the conversion rates of catalytic degradation reach 74%, 78% and 92%, and a degradation product and a catalyst are completely separated after the catalytic degradation is completed, so that the product and the catalyst are convenient to recycle and reuse.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic waste recycling, and in particular to an application of a zirconium-based metal organic framework in the degradation of PET plastic, a molybdenum-loaded zirconium-based metal organic framework and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (PET) is one of the most widely used plastics, with an annual output of nearly 70 million tons, and is widely used in the production of fibers, beverage bottles and food packaging. However, a large number of PET products after use are not effectively recycled. It is reported that only 42% of PET bottles are recycled, and the rest are landfilled or incinerated. Due to the accumulation of PET plastic in the environment, it is economically and environmentally critical to develop effective recycling methods to deal with the rapidly accumulated PET.

[0003] At present, the main methods for recycling PET are physical methods and chemical methods. The products recycled by physical methods are mostly low-grade plastics with poor optical, thermal and mechanical properties. The chemical method is to degrade PET into small molecular monomers or oligomers. At present, the main chemical recycling methods for PET are hydrolysis, alcoholysis, glycolysis and hydrogenolysis, but the methods such as hydrolysis, alcoholysis and glycolysis require the use of a large amount of solvents, high temperature and high pressure, and the degradation products are difficult to separate and purify.

[0004] CN 118561675 A uses ZnCl2 to catalyze the degradation of PET into precursor PTA, and the PTA yield reaches 92%. However, the patent performs catalytic degradation in an atmosphere containing chlorine and chlorine-containing gas, and the Cl2 and chlorine-containing gas used are both toxic, which has safety and environmental protection problems. At the same time, after the catalytic degradation is completed, the degradation products and the catalyst are mixed together, and ethanol cleaning is required to obtain the final degradation products. Metal organic frameworks (MOFs) are widely used in many fields such as gas storage, separation, and catalysis because of their diverse structures, high specific surface area, adjustable pore structure, and easy functional modification. In particular, in the field of catalysis, MOFs materials have the advantages of both homogeneous catalysts and heterogeneous catalysts, and show great potential in catalysis. However, there are few studies on the application of catalytic degradation of PET. Wu et al. decomposed PET into two monomers, terephthalic acid and monomethyl terephthalate, by using zirconium-based metal organic framework UiO-66. However, after the reaction, the structure of the used UiO-66 changed, and there was a problem of structural instability. Therefore, applying the structurally stable metal-organic framework to the chemical recycling of PET can solve the technical problems of harsh chemical recycling conditions of PET and difficulty in separating degradation products in the existing technology, and has broad application prospects. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide an application of a zirconium-based metal organic framework in the degradation of PET plastics, so as to solve the conditional limitations in the chemical recycling of PET plastics in the prior art, such as the need to use a large amount of solvents, high temperature and high pressure, and the difficulty in separating and purifying the degradation products.

[0006] Another object of the present invention is to provide a method for preparing a zirconium-based metal organic framework loaded with molybdenum.

[0007] Another object of the present invention is to provide a zirconium-based metal-organic framework loaded with molybdenum.

[0008] The method of the invention uses a zirconium-based metal organic framework NU-1000 with good chemical stability and thermal stability, and by loading Mo metal on NU-1000 and activating the loaded NU-1000 with hydrogen at high temperature, catalyzing PET plastic in a solvent-free atmosphere at one atmosphere of pressure to degrade the PET plastic into terephthalic acid (TA) and monomethyl terephthalate (MMT), and the degradation products are easily separated and recovered.

[0009] In order to achieve the above object, the present invention adopts the following technical solutions:

[0010] An application of a zirconium-based metal organic framework in the degradation of PET plastics, wherein the zirconium-based metal organic framework is used as a catalyst to catalyze the degradation of PET plastics;

[0011] The zirconium-based metal organic framework is at least one of NU-1000, Mo-NU-1000 and Mo-NU-1000-H2.

[0012] The PET plastic is PET plastic particles with a particle size of 200 meshes.

[0013] Preferably, the degradation conditions are as follows: the catalytic degradation atmosphere is hydrogen or nitrogen, and the amount of catalyst added is 1.5-5 mol%, more preferably 2.5 mol%, of the amount of PET plastic used.

[0014] Preferably, the temperature of the catalytic degradation is 260-270° C., the pressure is 1 atmosphere, and the degradation time is 12-24 hours.

[0015] Preferably, the NU-1000 is a zirconium-based metal-organic framework;

[0016] The Mo-NU-1000 is obtained by using NU-1000 as a parent material and introducing metallic molybdenum into the parent material using a solvothermal method;

[0017] The Mo-NU-1000-H2 is obtained by subjecting Mo-NU-1000 to high-temperature activation treatment with hydrogen.

[0018] Preferably, the conditions for the hydrogen high-temperature activation are: hydrogen pressure is one atmosphere, temperature is 260° C. to 270° C., and time is 8 h to 16 h.

[0019] The preparation method of Mo-NU-1000 and Mo-NU-1000-H2 in the above application comprises the following steps:

[0020] (1) dissolving NU-1000 and a metal molybdenum source in an organic solvent, heating and stirring the mixture for reaction, centrifuging the product to obtain a precipitate, washing and drying the precipitate to obtain Mo-NU-1000;

[0021] (2) Mo-NU-1000 is placed in a reaction tube, which is sealed, and the air in the reaction tube is purged with hydrogen. The reaction tube is then placed in a hydrogen atmosphere for activation to obtain a molybdenum-loaded metal organic framework Mo-NU-1000-H2.

[0022] Preferably, the metal molybdenum source in step (1) is one of molybdenum acetylacetonate, molybdenum acetate and molybdenum pentachloride, and the molar ratio of NU-1000 to the metal molybdenum source is 1:4 to 8, more preferably 1:4.

[0023] Preferably, the reaction temperature in step (1) is 50-60° C., and the stirring time is 7-12 h;

[0024] The drying is vacuum drying at a temperature of 110 to 150° C. for a time of 12 to 16 hours.

[0025] Preferably, the washing in step (1) is washing the product three times with methanol and dichloromethane respectively.

[0026] Preferably, the organic solvent in step (1) is methanol or DMF.

[0027] A zirconium-based metal-organic framework Mo-NU-1000-H2 loaded with molybdenum is prepared by the above method.

[0028] Preferably, the specific surface area of ​​the molybdenum-loaded zirconium-based metal organic framework Mo-NU-1000-H2 is 1800-2200 m 2 / g, and the pore sizes are 1-1.5nm (micropores) and 2.5-3.5nm (mesopores).

[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0030] (1) The present invention uses zirconium-based metal organic framework NU-1000 as the matrix material for catalytic degradation of PET plastics. By introducing metal molybdenum and high-temperature hydrogen activation, metal organic framework materials Mo-NU-1000 and Mo-NU-1000-H2 based on NU-1000 are obtained. These three materials have certain catalytic degradation effects on PET, and the catalytic degradation conversion rates can reach up to 74%, 78% and 92% respectively.

[0031] (2) Compared with the disadvantages of the prior art that a large amount of solvents, high temperature and high pressure are required, the present invention uses a 260-270°C, solvent-free and one atmosphere gas atmosphere as reaction conditions, which simplifies the PET plastic degradation process and is safer and more environmentally friendly.

[0032] (3) Compared with the problem of difficulty in separating and purifying degradation products in the prior art, after the catalytic degradation is completed, the degradation products and the catalyst are completely separated in the present invention, which is convenient for recycling and reuse of the products and the catalyst.

[0033] (4) The Mo-NU-1000-H2 of the present invention has a stable structure and does not change after catalytic degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the PXRD pattern of the catalyst prepared in Example 2.

[0035] Figure 2 This is a graph showing the nitrogen adsorption and desorption specific surface area of ​​the catalysts prepared in Examples 1 and 2.

[0036] Figure 3 SEM images of NU-1000, Mo-NU-1000, and Mo-NU-1000-H2 prepared in Examples 1 and 2.

[0037] Figure 4 PXRD patterns of Mo-NU-1000 and NU-1000 prepared in Example 1 after high temperature heating.

[0038] Figure 5 These are the XPS graphs of Mo-NU-1000 prepared in Examples 1 and 2 before and after hydrogen high-temperature activation. a and c are the Mo3d XPS spectra and fitting results of Mo-NU-1000 and Mo-NU-1000-H2, respectively. b and d are the Zr3d XPS spectra and fitting results of Mo-NU-1000 and Mo-NU-1000-H2, respectively.

[0039] Figure 6 This is a graph showing the conversion rate of PET plastic using different catalysts.

[0040] Figure 7This is a comparison chart of PET before and after catalytic degradation.

[0041] Figure 8 This is the H NMR spectrum of terephthalic acid (TA), a degradation product of PET.

[0042] Fig. 9 This is the H NMR spectrum of monomethyl terephthalate (MMT), a degradation product of PET. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.

[0044] NU-1000 was prepared according to the following method:

[0045] 98 mg of ZrOCl2·8H2O and 2 g of benzoic acid were added to 8 mL of DMF and dissolved by ultrasonication. Solution 1 was obtained after ultrasonic dissolution. Solution 1 was placed in an oven and reacted at 100°C for 1 hour. After the reaction, solution 1 was cooled to room temperature, 40 mg of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene and 40 μL of trifluoroacetic acid were added, and solution 2 was obtained after ultrasonication for 10 minutes. Solution 2 was placed in an oven and reacted at 100°C for 18 hours. After the reaction, solution 2 was cooled to room temperature, centrifuged to obtain sediment, and the sediment was washed three times with DMF, soaking for 1 hour each time. The washed product was mixed with 12 mL of DMF, and 0.5 mL of 8M hydrochloric acid was added, and solution 3 was obtained by ultrasonication. Solution 2 was placed in an oven and reacted at 100°C for 18 hours. After the reaction, the solution 3 was cooled to room temperature, and the sediment was obtained after centrifugation. The sediment was washed three times with DMF and methanol, respectively, and each washing was soaked for 1 hour. After washing, the product was vacuum dried at 130° C. for 12 hours to obtain NU-1000.

[0046] Example 1

[0047] Preparation of Mo-NU-1000:

[0048] 21.77 mg (0.01 mmol) of NU-1000 and 13.05 mg (0.04 mmol) of molybdenum acetylacetonate were dissolved in 2 mL of methanol, and the mixed solution was reacted at 60° C. under stirring for 7 h. The obtained product was centrifuged to obtain a sediment, which was then washed three times with methanol and dichloromethane respectively. After washing, the product was vacuum dried at 130° C. for 12 h to obtain Mo-NU-1000.

[0049] Example 2

[0050] The element valence state of Mo in Mo-NU-1000 is changed by high temperature activation with hydrogen, including the following steps:

[0051] The Mo-NU-1000 material was added into a sealed reaction tube, and the air in the tube was expelled by purging the reaction tube with hydrogen for 15 minutes. The reaction tube was then heated at 260°C for 12 hours in a hydrogen atmosphere at 1 atmosphere to obtain the activated Mo-NU-1000 material (denoted as Mo-NU-1000-H2).

[0052] Figure 1 The powder XRD pattern (PXRD) shows that the position of the characteristic peaks of Mo-NU-1000 has not changed significantly compared with that of NU-1000 material, indicating that Mo-NU-1000 retains the corresponding crystallinity and phase purity. Figure 2 The specific surface area of ​​nitrogen adsorption and desorption shows that the material after loading and activation also retains the corresponding pore structure. The material has the same microporous and mesoporous structure as the parent material NU-1000. The specific surface area of ​​Mo-NU-1000-H2 is 1825m 2 / g, and the pore sizes are 1.25nm (micropores) and 2.75nm (mesopores). Figure 3 The SEM images show that the three materials have the same rod-like structure and size. Figure 4 The powder XRD pattern (PXRD) shows that the crystallinity and phase purity of Mo-NU-1000-H2 did not change after high-temperature activation with hydrogen, and it has good structural stability. However, the structure of NU-1000 changed after high-temperature activation. Figure 5 The XPS graph shows that after high temperature activation, Mo-NU-1000-H2 has more Mo than Mo-NU-1000. 5+ The peak of indicates that high temperature hydrogen activation successfully changed the elemental valence state of metal Mo.

[0053] Example 3

[0054] Different from Example 2, the activated Mo-NU-1000 material (denoted as Mo-NU-1000-H2) was obtained by heating at 270°C for 8 hours.

[0055] Example 4

[0056] A method for catalytic degradation of PET plastic using a zirconium-based metal organic framework, 21.3 mg (0.11 mmol) of PET plastic particles were mixed with 11.9 mg (0.0055 mmol) of NU-1000, 12.6 mg (0.0055 mmol) of Mo-NU-1000, and 12.6 mg (0.0055 mmol) of Mo-NU-1000-H2 (Example 2) and added to a reaction tube, the amount of zirconium-based metal organic framework added was 5 mol% of the amount of PET plastic, and then the reaction tube was purged with H2 for 15 min, and a balloon filled with H2 was inserted above the reaction tube. The reaction tube was then placed in a heater, the heating temperature was controlled to 260 ° C, and the heating reaction was performed for 24 hours. After the reaction tube was cooled to room temperature, 1 mL of DMSO-d6 (dissolved product) and mesitylene (NMR internal standard) were added to the tube, and the yield was calculated by nuclear magnetic resonance hydrogen spectrum analysis. After calculation, the conversion rate of NU-1000 to PET plastic is 65%, the conversion rate of Mo-NU-1000 to PET plastic is 61%, and the conversion rate of Mo-NU-1000-H2 to PET plastic is 79%.

[0057] Example 5

[0058] A method for catalytic degradation of PET plastic using a zirconium-based metal organic framework, 21.3 mg (0.11 mmol) of PET plastic particles were mixed with 6 mg (0.00275 mmol) of NU-1000, 6.3 mg (0.00275 mmol) of Mo-NU-1000, and 6.3 mg (0.00275 mmol) of Mo-NU-1000-H2 (Example 2) and added to a reaction tube, the amount of zirconium-based metal organic framework added was 2.5 mol% of the amount of PET plastic, and then the reaction tube was purged with H2 for 15 min, and a balloon filled with H2 was inserted above the reaction tube. The reaction tube was then placed in a heater, the heating temperature was controlled to 260 ° C, and the heating reaction was performed for 24 hours. After the reaction tube was cooled to room temperature, 1 mL of DMSO-d6 (dissolved product) and mesitylene (NMR internal standard) were added to the tube, and the yield was calculated by nuclear magnetic resonance hydrogen spectrum analysis. After calculation, the conversion rate of NU-1000 to PET plastic is 74%, the conversion rate of Mo-NU-1000 to PET plastic is 78%, and the conversion rate of Mo-NU-1000-H2 to PET plastic is 92%.

[0059] Comparison of PET before and after catalytic degradation (see Figure 6 ) It can be seen that the degradation products and the catalyst are completely separated, and the final degradation products do not need to be washed and separated by adding organic solvents, and the degradation products can be obtained directly by scraping.

[0060] Example 6

[0061] A method for catalytic degradation of PET plastic using a zirconium-based metal organic framework, 21.3 mg (0.11 mmol) of PET plastic particles were mixed with 6 mg (0.00275 mmol) of NU-1000, 6.3 mg (0.00275 mmol) of Mo-NU-1000, and 6.3 mg (0.00275 mmol) of Mo-NU-1000-H2 (Example 2) and added to a reaction tube, the amount of zirconium-based metal organic framework added was 2.5 mol% of the amount of PET plastic, and then the reaction tube was purged with N2 for 15 min, and a balloon filled with N2 was inserted above the reaction tube. The reaction tube was then placed in a heater, the heating temperature was controlled to 260 ° C, and the heating reaction was performed for 24 hours. After the reaction tube was cooled to room temperature, 1 mL of DMSO-d6 (dissolved product) and mesitylene (NMR internal standard) were added to the tube, and the yield was calculated by nuclear magnetic resonance hydrogen spectrum analysis. After calculation, the conversion rates of NU-1000, Mo-NU-1000 and Mo-NU-1000-H2 to PET plastics are 55%, 57% and 68% respectively.

[0062] Example 7

[0063] Different from Example 5, 21.3 mg (0.11 mmol) of PET plastic particles were mixed with 3.6 mg (0.0017 mmol) of NU-1000, 3.9 mg (0.0017 mmol) of Mo-NU-1000, and 3.9 mg (0.0017 mmol) of Mo-NU-1000-H2 (Example 2) and added to the reaction tube. The amount of zirconium-based metal organic framework added was 1.5 mol% of the amount of PET plastic. The reaction tube was then purged with H2 for 15 min, and a balloon filled with H2 was inserted above the reaction tube. The reaction tube was then placed in a heater, the heating temperature was controlled to 260° C., and the heating reaction was performed for 24 h. After the reaction tube was cooled to room temperature, 1 mL of DMSO-d6 (dissolved product) and mesitylene (NMR internal standard) were added to the tube, and the yield was calculated by NMR hydrogen spectrum analysis. After calculation, the conversion rate of NU-1000 to PET plastic is 61%, the conversion rate of Mo-NU-1000 to PET plastic is 68%, and the conversion rate of Mo-NU-1000-H2 to PET plastic is 77%.

[0064] Example 8

[0065] The difference from Example 5 is that the heating temperature is controlled to be 270° C. and the heating reaction is carried out for 24 hours. After calculation, the conversion rate of the zirconium-based metal organic framework to PET plastic is equivalent to the result of Example 5.

[0066] Comparative Example 1

[0067] Mo-NU-1000 was activated by nitrogen at high temperature. The Mo-NU-1000 material was added into a reaction tube and sealed. The reaction tube was purged with nitrogen for 15 minutes to expel the air in the tube. The reaction tube was then heated at 260°C for 12 hours in a nitrogen atmosphere at 1 atmosphere to obtain the activated Mo-NU-1000 material (denoted as Mo-NU-1000-N2).

[0068] 21.3 mg (0.11 mmol) of PET plastic particles and 12.6 mg (0.0055 mmol) of Mo-NU-1000-N2 were mixed and added to a reaction tube. The amount of zirconium-based metal organic framework added was 5 mol% of the amount of PET plastic used. The reaction tube was then purged with H2 for 15 min, and a balloon filled with H2 was inserted above the reaction tube. The reaction tube was then placed in a heater, the heating temperature was controlled to 260°C, and the heating reaction was performed for 24 h. After the reaction tube was cooled to room temperature, 1 mL of DMSO-d6 (dissolved product) and mesitylene (NMR internal standard) were added to the tube, and the yield was calculated by NMR hydrogen spectrum analysis. After calculation, the conversion rate of Mo-NU-1000-N2 in Comparative Example 1 to PET plastic was only 59%.

[0069] Comparative Example 2

[0070] Without adding any catalyst, 21.3 mg (0.11 mmol) of PET plastic particles were added to the reaction tube, and then H2 was purged into the reaction tube for 15 minutes, and a balloon filled with H2 was inserted above the reaction tube. The reaction tube was then placed in a heater, the heating temperature was controlled to 260°C, and the heating reaction was carried out for 24 hours. After the reaction tube was cooled to room temperature, 1 mL of DMSO-d6 (dissolved product) and mesitylene (NMR internal standard) were added to the tube, and the yield was calculated by NMR hydrogen spectrum analysis. After calculation, the conversion rate of PET plastic was only 11%.

[0071] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. Application of a zirconium-based metal organic framework in the degradation of PET plastics, characterized in that: The zirconium-based metal organic framework is used as a catalyst to catalyze the degradation of PET plastic; The zirconium-based metal organic framework is at least one of NU-1000, Mo-NU-1000 and Mo-NU-1000-H2.

2. The use according to claim 1, characterized in that: The conditions for the catalytic degradation are as follows: the catalytic degradation atmosphere is hydrogen or nitrogen, and the amount of the catalyst added is 1.5-5 mol% of the amount of PET plastic used.

3. The use according to claim 1, characterized in that: The temperature of the catalytic degradation is 260-270°C, the pressure is 1 atmosphere, and the catalytic degradation time is 12-24 hours; The NU-1000 is a zirconium-based metal-organic framework; The Mo-NU-1000 is obtained by using NU-1000 as a parent material and introducing metallic molybdenum into the parent material using a solvothermal method; The Mo-NU-1000-H2 is obtained by subjecting Mo-NU-1000 to high-temperature activation treatment with hydrogen.

4. The use according to claim 3, characterized in that: The conditions for the hydrogen high temperature activation are: the hydrogen pressure is one atmosphere, the temperature is 260° C. to 270° C., and the time is 8 h to 16 h.

5. The method for preparing Mo-NU-1000-H2 in any one of claims 1 to 4, comprising the following steps: (1) dissolving NU-1000 and a metal molybdenum source in an organic solvent, heating and stirring the mixture for reaction, centrifuging the product to obtain a precipitate, washing and drying the precipitate to obtain Mo-NU-1000; (2) Mo-NU-1000 is placed in a reaction tube, which is sealed, and the air in the reaction tube is purged with hydrogen. The reaction tube is then placed in a hydrogen atmosphere for activation to obtain a molybdenum-loaded metal organic framework Mo-NU-1000-H2.

6. The preparation method according to claim 5, characterized in that: The metal molybdenum source in step (1) is one of molybdenum acetylacetonate, molybdenum acetate and molybdenum pentachloride, and the molar ratio of NU-1000 to the metal molybdenum source is 1:4-8.

7. The preparation method according to claim 5, characterized in that: The reaction temperature in step (1) is 50-60° C. and the stirring time is 7-12 h; The drying is vacuum drying at a temperature of 110 to 150° C. for a time of 12 to 16 hours.

8. The preparation method according to claim 5, characterized in that: The washing in step (1) is washing the product three times with methanol and dichloromethane respectively.

9. The preparation method according to claim 5, characterized in that: The organic solvent in step (1) is methanol or DMF.

10. A zirconium-based metal-organic framework Mo-NU-1000-H2 loaded with molybdenum, characterized in that: The method is prepared by any one of claims 5 to 9.

Citation Information

Patent Citations

  • Method for recycling precursor PTA (pure terephthalic acid) through catalytic degradation of PET (polyethylene terephthalate)

    CN118561675A